Selected Oxidative Stress Markers in Colorectal Cancer Patients in Relation to Primary Tumor Location—A Preliminary Research - Karolina Janion; Elżbieta Szczepańska; Ewa Nowakowska-Zajdel; Joanna Strzelczyk; Angelika Copija (Medicina, 2020)
Background and objectives: Ample evidence indicates that oxidative stress, including complex lipid peroxidation processes, may play a significant role in the pathogenesis of colorectal cancer. The goal of this study was to evaluate selected oxidative stress markers in patients with colorectal cancer depending on some clinical features, with particular attention paid to the location of the primary tumor. Materials and Methods: The study was conducted on a group of 66 patients with colorectal cancer. The study consisted of two stages. The first stage involved the analysis of medical records; the second consisted of determining selected oxidative stress markers by measuring malondialdehyde as well as total oxidant and antioxidant status. Results: Of all patients, 43 (65.15%) had colon cancer, of whom 30 (69.77%) had a tumor on the left side and 13 (30.23%) had a tumor on the right side of the colon. Of all the patients, 23 (34.85%) had rectal cancer. The mean total oxidant and antioxidant status was 809.76 (SD ± 392.65) µmol/L and 253.19 (233.33−310.66) µmol/L, respectively. The mean malondialdehyde serum level was 2478.04 (SD ± 1397.05) ng/mL. The mean malondialdehyde serum concentration in patients with primary tumors located on the right side was higher in a statistically significant way compared with the remaining patients. Conclusions: It was demonstrated that the intensity of lipid peroxidation processes is correlated with the development of colorectal cancer, particularly on the right side. The results should be interpreted rather cautiously due to certain limitations of the study.